Good Work and Good Works: Work and the Postsecular in George Saunders’s CivilWarLand in Bad Decline - Brian Jansen; Hollie Adams (European Journal of American Studies)
Drawing on what American short story writer and novelist George Saunders has described as the urge toward kindness in his work, as well as its myriad allusions to Christian symbology and religiosity, this paper explores the intersection of languages of labour or “work” and religious tensions in Saunders’ oeuvre. Reading the stories of Saunders’s first collection, CivilWarLand in Bad Decline, through the lens of postsecular literary theory and Saunders’s own comments on Catholicism, we suggest that Christianity, for Saunders, is a double-edged sword: crucial to his social critique of the power structures of post-industrial, postmodern life, and yet ultimately prone, in its institutionalized forms, to cooptation by those very same power structures. Saunders’s “Center for Wayward Nuns” is a potent metaphor in the sense that it suggests that doubt and lack of agency endemic to a fragmented postmodern world do not absolve us of our ethical responsibility, and thus the Christian overtones of Saunders’ work are engaged in a compelling kind of double-critique: both of the “un-Christian” social realities of the world in which Saunders’ working poor toil, but also of the kind of extremist, fundamentalist—even corporatized—Christianity that may emerge out of those social realities.